The structure, content and context of achieved celebrity brands: A study of footballers in their brandscapes - Zarkada, Anna K.; Tzoumaka, Eugenia (My University, 2020)
Celebrity athletes are the most prominent achieved celebrity brands with well-noted effects in consumer behaviour. Still, current research is characterised by terminological polyglossia and conceptual overlaps, which results in a lack of clarity regarding the brand structure and content. Moreover, there is no consideration of the brandscape; the team or sports club the player belongs to or has most closely associated his name with. This paper addresses the current limitations by adopting an exploratory approach. Through qualitative research, namely five focus groups, we empirically investigated the celebrity footballer brand associations as they are being perceived by keen football fans. The data demonstrate that the celebrity footballer brand comprises two distinct components proposed by Keller (1993): 1) the professional one, to include product-related associations, further distinguished into individual, organisational and contextual associations; 2) the personal one, which corresponds to non-product-related associations and reflects the balance of a person's perceived virtues and vices. The role of the brandscape emerges as affecting his professional and personal associations both positively and negatively.
Keywords: Celebrities; Brand associations; Brandscape; Focus groups; Football; Human brands; Sports celebrities; Qualitative research